(untitled) (Research, Society and Development, 2022)
Introduction: Systemic arterial hypertension (SAH) is a chronic, non-communicable, multifactorial disease associated with factors such as anxiety. Anxiety behaves differently between men and women. Thus, the present study evaluated gender differences in anxiety and unscheduled visits in hypertensive patients. Method: Observational study was carried out with 1000 hypertensive volunteers (age: 61.0 ± 12.5). Through a questionnaire, sociodemographic and clinical data on unscheduled visits to urgency and anxiety were collected. Anxiety was assessed using the State-Trait Anxiety Inventory (STAI). Results: We observed that females are significantly higher in the presence of comorbidities (h=0.134; p=0.036), diabetes mellitus (h=0.137; p=0.034), dyslipidemia (h=0.137; p=0.032), depression (h=0.240, p=0.001), buy medication at a popular pharmacy (h=0.240; p<0.001), self-medication (h=0.200; p=0.002), unscheduled visit and trait anxieties (h=0.290; p<0.001) and status (h=0.239; p<0.001). In the multivariate analysis, males are more likely to have unscheduled visits (OR: 1.43 (95%CI: 1.07-1.92), p=0.015), and females are more likely to have trait anxiety (OR: 1.59 (95%CI: 1.21-2.09) p=0.001) and state anxiety (OR: 1.40 (95%CI: 1.06-1.85) p=0.016). Conclusion: In conclusion, although women are more anxious, both State and Trait, men are the ones who most seek unscheduled visits to the emergency room.